2003
DOI: 10.1289/ehp.5712
|View full text |Cite
|
Sign up to set email alerts
|

The temporal pattern of respiratory and heart disease mortality in response to air pollution.

Abstract: Short-term changes in ambient particulate matter with aerodynamic diameters < 10 micro m (PM10) have been associated with short-term fluctuations in mortality or morbidity in many studies. In this study, we tested whether those deaths are just advanced by a few days or weeks using a multicity hierarchical modeling approach for all-cause, respiratory, and cardiovascular deaths, for all ages and stratifying by age groups, within the APHEA-2 (Air Pollution and Health: A European Approach) project. We fit a Poisso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
159
0
13

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(186 citation statements)
references
References 43 publications
14
159
0
13
Order By: Relevance
“…Distributed lag models have long been used in econometrics 210,211 and have more recently been applied in air pollution epidemiology. 31,212 Studies using distributed lag models to evaluate associations from 5 to Յ60 days after exposure have been conducted using data from 10 U.S. cities, 213,214 European cities from the APHEA-2 project, 215,216 and Dublin. 217 In all of these analyses, the net PM-mortality effect was larger when time scales longer than a few days were used.…”
Section: Daily Time Series Studies With Longer Time Scales or Extendementioning
confidence: 99%
“…Distributed lag models have long been used in econometrics 210,211 and have more recently been applied in air pollution epidemiology. 31,212 Studies using distributed lag models to evaluate associations from 5 to Յ60 days after exposure have been conducted using data from 10 U.S. cities, 213,214 European cities from the APHEA-2 project, 215,216 and Dublin. 217 In all of these analyses, the net PM-mortality effect was larger when time scales longer than a few days were used.…”
Section: Daily Time Series Studies With Longer Time Scales or Extendementioning
confidence: 99%
“…The short-term effects of air pollution were quantified in two large studies conducted in the United States [15,16] [17,18]. The NMM-APS collected data on outcomes in 50 million people in the 20 largest cities.…”
Section: Effects On Mortalitymentioning
confidence: 99%
“…Additional analyses of the APHEA-2 mortality data, based on lag periods of up to 40 days, found that the risk of adverse health effects associated with air pollution more than doubled (e.g. a 1.97% increase in mortality per 10-lg m -3 elevation in PM 10 ) [18]. The APHEA project also examined the association between airborne particles and hospital admission for cardiac causes in eight European cities [19] and found that the percentage increases associated with a 10-lg m -3 elevation in PM 10 were 0.5% for cardiac admissions in people of all ages and 0.7% for cardiac admissions in people older than 65 years.…”
Section: Effects On Mortalitymentioning
confidence: 99%
“…Usually applied to social sciences studies and econometrics, the use of this approach in epidemiology has been described in air pollution time series. 3,16 In this study, it was investigated the lag structure of air pollution and weather effects on cardiovascular hospital admissions using a third degree polynomial with 21 days, from lag zero to lag 20, which imposes constraints, but gives enough flexibility to estimate a biologically plausible lag structure, and controlling multicollinearity better than an unconstrained lag model. The standard errors of the estimates for each day were adjusted for overdispersion.…”
Section: Dailymentioning
confidence: 99%
“…Compared to respiratory diseases, cardiovascular effects due to PM 10 were found to be more acute with adverse responses seen at the same day or, at the most, on the subsequent day. Recently, investigating the effects of PM 10 on cardiovascular diseases deaths in European cities, Zanobetti et al 16 used a longer distributed lag model, from day zero to day 40, and showed a five-time higher effect than that estimated for the day and day after exposures only. It is highly relevant for estimates of air pollution attributed adverse effects on health.…”
Section: Introductionmentioning
confidence: 99%